A multidimensional and nitrogen-doped graphene/hierarchical porous carbon as a sulfur scaffold for high performance lithium sulfur batteries. (10th July 2018) - Wu, Huali; Xia, Li; Ren, Juan; Zheng, Qiaoji; Xie, Fengyu; Jie, Wenjing; Xu, Chenggang; Lin, Dunmin
Abstract: Constructing 3D heteroatom-doped carbon framework from sp 2 -hybridized nanocarbon (graphene) and sp 3 -hybridized porous carbon (activated carbon) has been considered as an effective method to achieve excellent performance in energy conversion and storage due to the synergistic effect between building blocks. Herein, a facile assembly of graphene oxide and porous carbon is reported to fabricate the inherent nitrogen-doped porous carbon and graphene composited nanostructures. When used as the sulfur scaffold for lithium sulfur batteries, the materials suggest outstanding electrochemical properties, including a high reversible capacity (1372 mAh g −1 at 0.1C), excellent rate performance (451 mAh g −1 at 3C) and cycling stability (579 mAh g −1 at 1C after 500 cycles). The enhancement in electrochemical properties can be ascribed to the 3D hierarchical porous structure of the carbon hybrid, in which, besides, the inherent doping of nitrogen can generate homogeneous active sites and defects that can effectively improve the interfacial adsorption. Thus, the simple strategy of pyrolysis and self assembly of graphene oxide and porous carbon provided in this work opens a new avenue for combining different dimensional nanocarbons to construct nitrogen-doped, multi-dimensional carbon architecture for high performance lithium sulfur batteries.